Fiscal deficit and its impact on economic growth: Evidence from Bangladesh - Mohammed Ershad Hussain; Mahfuzul Haque (Economies, 2017)
The findings from the VECM for BBS data reveal that there is a positive and significant relationship between FD and GDPGR, supporting the Keynesian theory, while findings from the VECM for World Bank data indicate that the impact of Fiscal Deficit (FD) on GDPGR is mild but negative and significant at the 5% level. This contradicts the Keynesian theory, but is in accord with Neo-classical theory which asserts that fiscal deficits lead to a drop in the GDP. Nevertheless, the government must strive to keep deficit under control, not to hamper growth, and expenditure ought to be set so as to avoid massive deficits leading to debt financing and the crowding-out effect of private investment. If deficits become unsustainable, it can lead to higher interest payments, and the government may well default. Although in the economic literature, there is no definitive conclusion as to whether fiscal deficit helps or hinders economic growth for any country, many argue that fiscal deficit leads to economic growth of a country, which cannot be achieved only through domestic savings, not enough for investment. It can be assumed safely that to some extent fiscal deficit is good for economic growth if the borrowed money is spent on beneficial projects, provided the return from such investments exceeds the funding cost. For future research work, it will be interesting to examine the relationships between government spending, economic growth and long-term interest rate for Bangladesh.
Keywords: E62; F43; H61; H62; O40; 330; Fiscal Deficit; GDP; Vector Error Correction Model; Augmented Dickey Fuller and Bangladesh